2020
DOI: 10.1007/s10096-020-03978-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of the serological test in the diagnosis of 2019 novel coronavirus (SARS-CoV-2) infections during the COVID-19 outbreak

Abstract: We developed a chemiluminescence immunoassay method based on the recombinant nucleocapsid antigen and assessed its performance for the clinical diagnosis of severe acute respiratory syndrome coronavirus (SARS-CoV)-2 infections by detecting SARS-CoV-2-specific IgM and IgG antibodies in patients. Full-length recombinant nucleocapsid antigen and tosyl magnetic beads were used to develop the chemiluminescence immunoassay approach. Plasmas from 29 healthy cohorts, 51 tuberculosis patients, and 79 confirmed SARS-CoV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 20 publications
1
56
1
5
Order By: Relevance
“…Many serological enzyme-linked immunosorbent assays (ELISAs) have been developed recently to detect anti-SARS-CoV-2 antibodies. However, these assays have important limitations 4,8,[10][11][12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Many serological enzyme-linked immunosorbent assays (ELISAs) have been developed recently to detect anti-SARS-CoV-2 antibodies. However, these assays have important limitations 4,8,[10][11][12][13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…6 Initial positive rapid antibody test was considered false-positive. [7][8][9][10][11][12] On the other hand, chest CT has been proposed as a diagnostic criterion by the National Health Commission of China in Hubei with the benefit of advancing proper treatment and isolation measures due to the delays of microbiological testing. Also, some studies have suggested that chest CT may have higher sensitivity for diagnosis of COVID-19 than RT-PCR, and may have a role as the first step in diagnosis and follow-up to clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies are proteins generated by the immune system in response to an infection. The level of antibody response can vary with age, gender, and presence of comorbidities [123,124]. Immunoglobulin G, M, and A (IgG, IgM, and IgA) are being used as potential markers for COVID-19.…”
Section: Antibody-based Testsmentioning
confidence: 99%
“…Analysis of sequencing data from clinical samples (using Illumina sequencer) unveiled undetected community transmission of COVID-19 in the state of Washington [72] Analysis of sequencing data from clinical samples (using Illumina sequencer) unveiled multiple routes of introduction of COVID-19 into the state of California [73] Amplicon-based targeted sequencing from clinical samples (using Nanopore sequencer) unveiled multiple routes of introduction of COVID-19 into the Netherlands [102] Platforms and global consortiums utilizing genomic data to track real-time spread and evolution of pathogens including COVID-19 [84,103,104] immunoassay (CLIA) [123][124][125], and enzyme-linked immunosorbent assay (ELISA) [126,[133][134][135][136]. Pan et al [137] and Li et al [130] reported the detection of SARS-CoV-2 antibodies from whole blood.…”
Section: Antibody-based Testsmentioning
confidence: 99%